A case of laparoscopic anterior resection for rectal cancer with duplication of the inferior vena cava using preoperative 3D computed tomography angiography. Issue 9 (21st September 2020) - Furutani, Akinobu; Yoshida, Sachiko; Yoshida, Toshihiko; Nishi, Masayasu; Yamagishi, Takashi; Goto, Hironobu; Otsubo, Dai; Yamane, Hisoka; Matsumoto, Taku; Fujino, Yasuhiro; Tominaga, Masahiro
Abstract: We report the case of a patient with duplication of the inferior vena cava (DIVC) who underwent anterior laparoscopic resection for rectal cancer. A 66-year-old woman presented with abnormal lung shadows on a chest x-ray during a routine health checkup. She was diagnosed with rectal cancer and lung metastasis using colonoscopy and thoracoabdominal computed tomography (CT). In addition, a 3D CT angiography revealed double inferior vena cava, one on either side of the aorta. The preoperative diagnosis was rectal cancer cT3N0M1a(Lung) cStage IVA with DIVC, and a two-stage surgery was planned. The first stage was high anterior laparoscopic resection. This was safely performed because the pre-hypogastric nerve fascia was preserved and the left inferior vena cava was not visualized during the surgery. During the second stage of the surgery, video-assisted thoracoscopic left lower lobectomy was performed and no recurrence was observed for >6 months after the second surgery.